Modeling Organizational Mediation A STEM Analysis of Work-Life Balance Determinants - Hendratmoko; Elisabeth Vita Mutiarawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Institut Bisnis dan Informatika Kwik Kian Gie, 2025)
This study aims to examine the influence of individual and organizational factors on work-life balance (WLB) as well as the mediating role of organizational factors, and the relationship between individual factors and WLB. This study uses a quantitative method with a total of 165 respondents working in Jakarta during December 2025. Data analysis using PLS-SEM. The results showed that individual factors had a significant effect on WLB (β=0.570) and organizational factors (β=0.650). Organizational factors also had a strong direct effect on WLB (β=0.518). This study also proves that organizational factors function as significant partial mediators with indirect effects = 0.337. This update in the research understands and confirms the mediation mechanism of organizational factors. Implicitly, organizational policies and culture need to be developed to reinforce individual factors towards WLB.